Epizootic canine distemper virus infection among wild mammals - Kameo, Yuki; Nagao, Yumiko; Nishio, Yohei; Shimoda, Hiroshi; Nakano, Hitoshi; Suzuki, Kazuo; Une, Yumi; Sato, Hiroshi; Shimojima, Masayuki; Maeda, Ken (Veterinary microbiology, 2012)
In the spring of 2007, seven raccoon dogs and a weasel were captured near the city of Tanabe in Wakayama prefecture, Japan. The causative agent of the animals’ death 1–2 days after capture was identified as canine distemper virus (CDV) by virus isolation, immunostaining with an anti-CDV polyclonal antibody, and a commercially available CDV antigen-detection kit. Sequence analysis of hemagglutinin genes indicated the isolated viruses belong to genotype Asia-1 and possess the substitution from tyrosine (Y) to histidine (H) at position 549 that is associated with the spread of CDV to non-canine hosts. A serosurvey for CDV was then conducted among wild animals in the region. The animals assayed consisted of 104 raccoons, 41 wild boars, 19 raccoon dogs, five Sika deer, two badgers, one weasel, one marten, one Siberian weasel and one fox. Virus-neutralization (VN) tests showed that, except for fox and weasel, all of the species assayed had VN antibodies to CDV. Interestingly, 11 of the 41 wild boars (27%) and two of the five Sika deer assayed possessed VN antibodies to CDV. These findings indicate that CDV infection was widespread among wild mammals during this epizootic.